Chemical Castration of Child Molesters – Right or Wrong?! - Ratkoceri, Vedije (European Journal of Social Science Education and Research, 2021)
Studies have shown that recidivism rates among child sexual offenders are very high. Therefore, the number of children victimized by paedophiles is also very high. In most of the cases, offenders committing these crimes suffer from paraphilia – categorized as a mental disorder by the psychological sciences. Thus, imprisonment for this category of child abusers obviously is not the answer. That’s why a lot of states have tried to incorporate in their legislations a medical treatment useful to prevent recidivism of paedophiles and to protect the children. Chemical castration is merely a type of hormone therapy that takes away the offender’s sexual desire. There can be some unpleasant side effects, but they are mostly reversible and this paper tries to argue that this procedure is humane and necessary to prevent child molesters. The first part of this paper examines paedophilia, chemical castration procedure and will show data from studies made mostly in USA to see the efficiency of this procedure. The second part of this paper examines the growing trend by legislators towards favoring castration as a sentencing alternative and explains the reasons for this trend. This part finds that this trend is a necessary response to a failing criminal justice system.